Liberalization Process of the EU Electricity Market - Šátralová, Aneta; Klosová, Anna, 1942-; Jegers, Marc; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2011)
This Master Thesis conducts a survey of the process of the liberalization of the electricity market, exclusively in the context of the European Union. The method of the review of the contemporary literatury is used to analyze reforms in the electricity supply industry. The thesis provides readers with the basic characteristics of the liberalization of this strategic net industry. The main focus is on one particular reform-unbundling- as it influences all principles of the eletricity energy markets. Scholars argue there are direct advantages and at the same time direct disadvanatges resulting from these reforms and it is almost impossible to find a clear agreement on if positive or negative effects prevails. In the thesis there is an attempt to evaluate whether contemporary research literature is able to decide if the liberalization reforms will bring about pure benefits for participants of the electricity markets.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of international trade and european integration [obor dipl. práce]